2016
DOI: 10.1007/s11356-016-7798-3
|View full text |Cite
|
Sign up to set email alerts
|

Atrazine, triketone herbicides, and their degradation products in sediment, soil and surface water samples in Poland

Abstract: The aim of this study was to monitor the sediment, soil and surface water contamination with selected popular triketone herbicides (mesotrione (MES) and sulcotrione(SUL)), atrazine (ATR) classified as a possible carcinogen and endocrine disrupting chemical, as well as their degradation products, in Silesia (Poland). Seventeen sediment samples, 24 soil samples, and 64 surface water samples collected in 2014 were studied. After solid-liquid extraction (SLE) and solid phase extraction (SPE), analytes were determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(35 citation statements)
references
References 57 publications
0
33
1
1
Order By: Relevance
“…The widespread use of atrazine throughout the season determines a diffuse occurrence, as described for glyphosate and by Quaghebeur et al [30], although the lower doses used in comparison with those of glyphosate are reflected in the concentrations we found. Other factors affecting its presence in water samples are its low adsorption to soil [53] and its persistence and ease of movement in the environment by drift, leaching or runoff [54], behavior similar to its secondary metabolites [55]. Thus, Solomon et al [56] collected half-life values of atrazine in water of 41-237 days and some authors reported residues of atrazine and its metabolites in surface and groundwater several years after use [51,57].…”
Section: Atrazine and Its Metabolites Hydroxyatrazine (Hoa) Deethylamentioning
confidence: 99%
“…The widespread use of atrazine throughout the season determines a diffuse occurrence, as described for glyphosate and by Quaghebeur et al [30], although the lower doses used in comparison with those of glyphosate are reflected in the concentrations we found. Other factors affecting its presence in water samples are its low adsorption to soil [53] and its persistence and ease of movement in the environment by drift, leaching or runoff [54], behavior similar to its secondary metabolites [55]. Thus, Solomon et al [56] collected half-life values of atrazine in water of 41-237 days and some authors reported residues of atrazine and its metabolites in surface and groundwater several years after use [51,57].…”
Section: Atrazine and Its Metabolites Hydroxyatrazine (Hoa) Deethylamentioning
confidence: 99%
“…Field channels and drainage systems associated with oilseed rape production were analysed for insecticide levels in Wielkopolska Province (Drożdżyński 2008). Additionally, the degradation products of atrazine were detected in sediments and surface waters of the Silesia region (Barchańska et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Beside good properties in the control of weeds, this herbicide is a potential pollutant, wherein sulcotrione and its degradation product (2-chloro-4-(methylosulfonyl) benzoic acid were detected in high concentrations in water from the Klodnica River in Poland. 12 Results of some studies have indicated that sulcotrione and/or its degradation products are toxic toward microorganism Vibrio fischeri, 13 genotoxic towards Allium cepa root meristem 14 and Vicia faba seedlings. 15 Considering that pesticides have a negative influence on living organisms, the need for their monitoring and control has become more obvious in recent years.…”
Section: Introductionmentioning
confidence: 99%